Alpha-synuclein inhibits poly (ADP-ribose) polymerase-1 (PARP-1) activity via NO-dependent pathway - Adamczyk, Agata; Kaźmierczak, Anna (Folia Neuropathologica, 2009)
α-Synuclein (ASN) is a brain-enriched protein that functions as a molecular chaperone and regulator of the synaptic vesicle cycle. However, if ASN is overexpressed and in prefibrillar oligomeric forms it activates free radical formation and has been implicated in neurodegeneration. The nuclear target for the free radical cascade is poly (ADP-ribose) polymerase-1 (PARP-1), a DNA-binding enzyme and transcriptional regulator that decides on cell survival or death. Our previous data indicated that soluble oligomeric form of ASN significantly stimulated nitric oxide synthase (NOS) activity and by oxidative stress leads to mitochondria failure and cell death. The aim of this study was to investigate the effect of ASN on PARP-1 protein level and on its activity in the rat brain using radiochemical and immunochemical methods. It was found that ASN (10 µM) had no effect on PARP-1 protein level. However, ASN inhibited this enzyme activity by 35% in rat brain cortex and hippocampus investigated together and in striatum by 18%. An inhibitor of constitutive NOS isoform, NG-nitro-L-arginine (NNLA, 100 µM), partially prevented ASN-evoked PARP-1 inhibition. The NO pool liberated by ASN could be involved in the decrease of PARP-1 activity. The direct interaction between ASN and PARP-1 protein should be taken into consideration.